Pasolini in Chiaroscuro - Sardes, Guillaume de 1979-; Pietromarchi, Bartolomeo 1968- (Flammarion, 2024)
Pasolini is perhaps the last European intellectual to have gained worldwide renown. A half-century on from his death, his influence can still be felt across the different fields in which he worked: he is read, commented on, adapted, and inspires contemporary creative artists. While he preferred to describe himself as a writer, it was his films that brought him to the public’s attention. Cinema, which acted as the perfect sounding board for his political ideas, occupies a central place in his oeuvre. And it is this aspect of his work, seen through the prism of the influence of classical and contemporary art on the aesthetic of his cinematographic work, that is the main focus of "Pasolini in chiaroscuro". Clips from Accattone, Théorème, Salò, and others are juxtaposed alongside paintings by Pontormo, Pieter Claesz, Giorgio Morandi, Fernand Léger, and Francis Bacon. Having first explored the way in which Pasolini drew on the work of painters from the past to compose his film sequences, the second part of the exhibition shows how the writer-director symmetrically inspired those who came after him. It brings together around thirty international artists who paid tribute to him, many of them having worked on his films
Published on the occasion of an exhibition at the Nouveau Musée National de Monaco, March 29-September 29, 2024
"with Adel Abdessemed, Giulia Andreani, Francis Bacon, Giacomo Balla, Tom Burr, Lodovico Cardi, Adam Chodzko, Pieter Claesz, Clara Cornu, Walter Dahn, Regina Demina, Marlene Dumas, Richard Dumas, Cerith Wyn Evans, Federico Fellini, Jesse A. Fernández, Abel Ferrara, Laurent Fiévet, Alain Fleisher, Claire Fontaine, Giovanni Fontana, Jenny Holzer, William Kentridge, Astrid Klein, Fernand Léger, Stéphane Mandelbaum, Martial, Fabio Mauri, Charles de Meaux, Giorgio Morandi, Dino Pedrali, Ernest Pignon-Ernest, Pontormo, Man Ray, Giuseppe Stampone, Jean-Luc Verna, Francesco Vezzoli, John Waters."--Museum website
Keywords: Pasolini, Pier Paolo -- 1922-1975; Pasolini, Pier Paolo / 1922-1975 / Exhibitions; Pasolini, Pier Paolo / 1922-1975 / Criticism and interpretation; Motion picture producers and directors / Italy / Exhibitions; Arts, Italian / 20th century; Pasolini, Pier Paolo / 1922-1975 / Critique et interprétation; Producteurs et réalisateurs de cinéma / Italie / Expositions; Arts italiens / 20e siècle; Pasolini, Pier Paolo / 1922-1975 / https://id.oclc.org/worldcat/entity/E39PBJbxCVvXMw9JB4JKBttxjC; Motion picture producers and directors; Arts, Italian; Italy / https://id.oclc.org/worldcat/entity/E39PBJvd8mVMcRhwVmbtcqCPcP; 1900-1999; exhibition catalogs; Exhibition catalogs; Criticism, interpretation, etc; Catalogues d'exposition; Ausstellungskatalog -- Nouveau Musée National de Monaco -- 29.03.2024-29.09.2024 -- Monaco